Hematological and Biochemical Effects Associated with Prolonged Administration of the NSAID Firocoxib in Adult Healthy Horses - Ignácio, Fernanda Saules [UNESP]; Garcia, Luana Venâncio; de Souza, Giovanna Gati; Amatti, Lidiana Zanetti; de Barros, Luiz Daniel; Bergfelt, Don R.; Camargo, Giovana Siqueira [UNESP]; de Meira, Cezinande [UNESP]; de Almeida, Breno Fernando Martins [UNESP] (MDPI, 2024)
Non-steroidal anti-inflammatory drugs (NSAIDs) represent one of the most commonly used classes of drugs in both human and veterinary medicine. However, many clinical side effects have been observed, especially when treatment has been prolonged. While the anti-inflammatory efficacy and safety of repeated administration of firocoxib (Previcox®), which is a selective NSAID COX-2 inhibitor, has been evaluated for short-term use (one to fourteen days), its clinical relevance for longer-term use is not known. As a preliminary study, healthy, adult male and female horses (n = 7) were treated with firocoxib for 40 days concomitant with the collection of blood samples encompassing treatment to assess hematological and biochemical endpoints. Daily oral administration of firocoxib was performed with one 57 mg tablet/animal (0.11–0.14 mg/kg), which was crushed and mixed with feed. Blood samples were collected one day before treatment (D0 or basal sample), during (D10, D20, D30, and D40), and after treatment (D55 and D70). Results indicated some hematological and biochemical effects were significantly reduced (p < 0.05) towards the end of treatment on D40 relative to pre-treatment or baseline values on D0. Post-treatment, all values returned to pre-treatment values within 30 days without any apparent clinical adversities. In conclusion, while these preliminary results are favorable for prolonged use of firocoxib in horses, future studies are required to evaluate the efficacy of prolonged use accompanied with other clinically relevant endpoints in healthy as well as injured or diseased animals.
Keywords: erythrogram; firocoxib safety; leukogram; long-term treatment; NSAID side effects; platelets